Between Compliance and Belonging: Navigating DEI in Restrictive Climates - Eric Z Glenn (The Political Librarian, 2025)
This paper reflects on the complexities of sustaining diversity, equity, and inclusion (DEI) work in a politicized higher education climate marked by anti-DEI legislation. Drawing from my experience as the inaugural Director of Organizational Development at Virginia Tech University Libraries, I explore how values of belonging and organizational well-being can be advanced even under restrictive conditions. The paper examines the tension between compliance and values, providing examples such as the transformation of the University Libraries Diversity Council into the Belonging and Wellness Council as a case study in adaptation. Regional insights from my role as Visiting Program Officer for the Association of Southeastern Research Libraries (ASERL) further demonstrate how external pressures reshape professional spaces for BIPOC librarians in a field that remains predominantly white. Ultimately, the paper argues that while legislation may shrink the space for equity work, it cannot erase the human need for belonging. Libraries, as institutions of access and trust, hold a responsibility to ensure that promise endures.
Keywords: Complinace; Belonging; DEI; Organizational Development